(untitled) (Medical Forum Monthly, 2022)
Objective: To discuss three years' experience with Senning operation and its short-term results. Study Design: retrospective study Place and Duration of Study: This study was conducted at the Children’s Hospital/ university of Child Health Sciences Lahore for a period of 03 years from January, 2019 to November, 2021. Materials and Methods: Record of all the patients who underwent Senning operation was reviewed. Age, sex, weight, pre-operative diagnosis, concomitant procedures, cross clamp time, bypass time, ICU stay were noted for each patient. Results: 41 patients had Senning operation for transposition of Great Arteries in last 3 years. 39 (95%) were successfully discharged home. Mean age was 4.2 years and mean weight was 10.5kg. Two patients died of low cardiac output. Conclusion: In developing countries where diagnosis of TGA is delayed due to multiple reasons, the Senning operation can make significant difference in the life of these patients. In the expert hands, it is safe and reproducible operation with good outcome.